The analysis of mutant phenotypes and tissue expression reveals a role of SNAREs VAMP721 and VAMP722 in seedling growth - L. Zhang; H. Y. Zhao; W. C. Qi; F. X. Zheng; T. Q. Wang; J. Y. Li (Biologia Plantarum, 2017)
Membrane traffic mediated by a soluble N-ethylmaleimide sensitive factor attachment protein receptor (SNARE) complex contributes to plant growth and development. However, the functional significance of SNAREs involved in cell wall deposition and seedling development has not been sufficiently explored. In this study, we explored the roles of R-SNAREs VAMP721 (At1g04750) and VAMP722 (At2g33120) in seedling growth of Arabidopsis thaliana by histochemical staining, fluorescence labeling, and analyzing mutant phenotypes. Our results show a massive intracellular accumulation of cellulose and callose, and an abnormal deposition of callose at the expanding cell plate in vamp721vamp722 root cells compared with the wild type. Particularly, ectopic lignin accumulation was also observed in vamp721vamp722 root cells. The alteration of cell wall components was confirmed using Fourier transform infrared analysis. Plasma membrane integrity and cell viability were disturbed in the vamp721vamp722 seedling. Morphological observation shows that vamp721vamp722 mutations impaired development of roots, hypocotyl, cotyledon, and true leaf, and inhibited lateral root formation. Confocal images reveal that green fluorescent protein-tagged VAMP721 and VAMP722 showed a similar expression pattern and were expressed throughout all cells and tissues examined, including root and shoot apical meristems and cells of hypocotyls, cotyledons, and true leaves. Taken together, our results suggest that membrane traffic mediated by VAMP721 and VAMP722 is involved in seedling growth in A. thaliana.